Populisme Agama: Analisis Dakwah dalam Konteks Politik Identitas di Era Modern - Sitti Ansoriah; Khusnul Khotimah (Universitas Islam Negeri Madura, 2025)
The purpose of this study is to look at the phenomenon of religious populism in the context of identity politics and how it impacts the approach to Islamic preaching in the digital era. Where there is a shift in Islamic preaching from a traditional approach to a more interactive and social media-based approach. This research was conducted using a descriptive qualitative approach through literature study. The results of the study show that religious populism increases social polarization and influences the content and style of preaching communication, which is more exclusive and emotional. In addition, the findings show that preachers (Dai) respond to this phenomenon in various ways, such as supporting populist narratives and preaching in a moderate manner to reduce social conflict. The new findings of this study lie in the strategic analysis of Islamic preaching in responding to religious populism from 2015 to 2024. By integrating the views of modern Muslim scholars on political communication, digital discourse, and da'wah theory. Previous studies have not discussed this approach comprehensively, especially those focusing on the dynamics of social media and religious identity. Therefore, it is hoped that this research will provide theoretical and practical assistance in building a da'wah strategy that is appropriate to the socio-political challenges in the digital era.